Double Burden Perempuan Penjual Ikan Di Awarangnge Desa Siddo Kecamatan Soppeng Riaja Kabupaten Barru (Suatu Kajian Sosiologi Gender) - Ibrahim, Mariamin (Phinisi Integration Review, 2018)
The objectives of this research are (i) To understand and analyze motivation that encourage women to do double roles in women fish sellers (ii) To understand and analyze the impact experienced by women fish sellers in implementing multiple roles. The type of this research is descriptive Quantitative research with research location in Siddo Village, Soppeng Riaja District of Barru Regency. Informants in this study are housewives who have multiple roles. Data collection techniques in research are interview, observation and documentation. Data analysis techniques in this study Purposive Sampling with criteria (i) married women, (ii) Women aged 30-50 Years, (iii) Women who work in the morning and in the afternoon. The results of this study indicate that the motivation that encourages women to do double roles in women fish sellers in Awarannge Siddo Village Soppeng Riaja District Barru Regency is Economic Factors (Financial Needs) and Educational Factors. While the impact of multiple roles performed by women fish sellers. Positive impacts include increasing household income as well as building a sense of mutual understanding among family members. While the negative impact of the lack of communication and socialization in the family and inheritance to the profession